Transport of root‐respired CO2 via the transpiration stream affects aboveground carbon assimilation and CO2 efflux in trees. Issue 2 (11th October 2012) - Bloemen, Jasper; McGuire, Mary Anne; Aubrey, Doug P.; Teskey, Robert O.; Steppe, Kathy
Summary: Upward transport of CO2 via the transpiration stream from belowground to aboveground tissues occurs in tree stems. Despite potentially important implications for our understanding of plant physiology, the fate of internally transported CO2 derived from autotrophic respiratory processes remains unclear. We infused a 13 CO2 ‐labeled aqueous solution into the base of 7‐yr‐old field‐grown eastern cottonwood ( Populus deltoides ) trees to investigate the effect of xylem‐transported CO2 derived from the root system on aboveground carbon assimilation and CO2 efflux. The 13 C label was transported internally and detected throughout the tree. Up to 17% of the infused label was assimilated, while the remainder diffused to the atmosphere via stem and branch efflux. The largest amount of assimilated 13 C was found in branch woody tissues, while only a small quantity was assimilated in the foliage. Petioles were more highly enriched in 13 C than other leaf tissues. Our results confirm a recycling pathway for respired CO2 and indicate that internal transport of CO2 from the root system may confound the interpretation of efflux‐based estimates of woody tissue respiration and patterns of carbohydrate allocation. Abstract : See also the Commentary by Trumbore et al